The Effect of Profitability and Company Size on Audit Delay at Banking Companies in 2020-2023 - Monika Handayani; Dina Indra Astuti (Cita Konsultindo Research Center, 2025)
This study aims to analyze the effect of profitability and company size on audit delay in banking companies in 2020-2023. This research is quantitative research. The data in this study are secondary data with sampling using purposive sampling method and obtained a sample of 13 banking companies in 2020-2023. The data analysis technique in this study used the Statistical Package for Social Science (SPSS) software program version 25 by performing the classical assumption test and multiple linear regression analysis. The results showed that Profitability (ROA) has no significant effect on Audit Delay while Company Size has a significant effect on Audit Delay